Retrospective analysis of the radiation situation in the territory of the Oryol region - V. G. Simonova; L. I. Bublikova (Радиационная гигиена)
The article considers the radiation situation in the Oryol region 33 years after the accident at the Chernobyl nuclear power plant. Since 1998, certification has made it possible to assess the main indicators of the radiation situation in the region and conduct a comparative analysis, evaluate the doses of the population from all the main sources and the effects of the radiation factor on public health, and determine the most significant directions for reducing the doses of the population. The contribution of man-made sources to the collective dose to the population of the Oryol region in 2017 was 0.73% according to radiation-hygienic certification, which is 3 times higher than in Russia (0.24%). This is primarily due to radioactive contamination of a part of the region after the Chernobyl accident. The Oryol region is one of fourteen oblasts of the Russian Federation affected by the accident at the Chernobyl nuclear power plant. As a result of this disaster, 22 out of 24 districts of the Oryol Oblast (about 40% of the oblast’s territory) were exposed to radioactive contamination to one degree or another. Differences in precipitation led to the formation of extremely spotted pollution in the Oryol region. 1243 people from the Oryol region took part in the liquidation of the Chernobyl accident. 43% of them became disabled 1, 2 and 3 groups, 115 people (9%) died within 14 years after these events. In the Oryol region, the radiation environment remains stable. The radiation background is between 0.12 and 0.19iSv/h, which corresponds to the values characteristic of the Oryol region before the Chernobyl accident. Comparison of radiation doses due to additional radiation for the 1st and 33rd years after the accident showed a 51-fold decrease due to the physical decay of long-lived radioisotopes and short-lived radionuclides, as well as their burial in the soil.